Lower transmissibility of SARS-CoV-2 among asymptomatic cases: evidence from contact tracing data in Oslo, Norway - Fredrik Methi; Elisabeth Henie Madslien (BMC Medicine, 2022)
Abstract Background Asymptomatic COVID-19 cases have complicated the surveillance and tracking of the pandemic. Previous studies have estimated that 15–25% of all infectees remain asymptomatic. Methods Based on contact tracing data from Oslo, Norway, we estimated transmission and susceptibility dynamics among symptomatic and asymptomatic cases and their contacts as identified by manual contact tracing between September 1, 2020, and September 1, 2021. Results Among 27,473 indexes and 164,153 registered contacts, the secondary attack rate (SAR-14) was estimated to be 28% lower through asymptomatic exposure (13%) compared to symptomatic exposure (18%). Furthermore, those infected by asymptomatic cases were almost three times more likely to be asymptomatic compared to those infected by symptomatic cases. Conclusions Symptomatic cases spread the virus to a greater extent than asymptomatic, and infectees are more likely to be asymptomatic if their assumed infector was asymptomatic.